Bureaucratic Reform of the Ngurah Rai Immigration Travel Documents Section, Realising Dynamic Immigration Governance - Herlis Fahmil Qur'ani; Ferdianty Augustinah; Eny Hartati (International Journal of Social Science and Humanity, 2026)
This study aims to examine the implementation of bureaucratic reform at the Immigration Document Section of Ngurah Rai Immigration Office, focusing on digital transformation through the M-Paspor application to realise a dynamic immigration management system. The research employed qualitative analysis to evaluate service efficiency, transparency, accountability, and staff capacity in the context of digital innovation aligned with Dynamic Governance principles. The findings reveal that digitalisation has significantly enhanced service efficiency through automated procedures, reduced physical queues, and improved transparency, whilst facilitating a shift from manual tasks to core verification and problem-solving activities, though challenges persist regarding human resources capacity and organisational culture, as staff exhibit rule-bound mindsets and defensive communication styles when addressing service delays, thereby undermining public trust and satisfaction. The study concludes that technology alone is insufficient to achieve truly responsive and citizen-centric services, as institutional culture and personnel mindset require continuous strengthening through soft skills training, ethical enforcement, and cultivation of service-oriented, empathetic work culture. Holistic reform approaches that combine technological innovation with human resource development and cultural change are essential for building effective, adaptive, and transparent immigration management systems. The integration of digital systems complemented by professional human resources can foster seamless, efficient, and trustworthy immigration services aligned with good governance principles, whilst sustainable improvements depend on balancing technological advances with organisational culture development and staff professionalism.